Direct observation of size scaling and elastic interaction between nano-scale defects in collision cascades - Yi, x; Sand, a; Mason, D; Kirk, M; Roberts, S; Nordlund, K; Dudarev, S (IOP Publishing, 2015)
Using in situ transmission electron microscopy, we have directly observed nano-scale defects formed in ultra-high-purity tungsten by low-dose high-energy self-ion irradiation at 30 K. At cryogenic temperature lattice defects have reduced mobility, so these microscope observations offer a window on the initial, primary damage caused by individual collision cascade events. Electron microscope images provide direct evidence for a power-law size distribution of nano-scale defects formed in high-energy cascades, with an upper size limit independent of the incident ion energy, as predicted by Sand et al. (EPL, 103 (2013) 46003). Furthermore, the analysis of pair distribution functions of defects observed in the micrographs shows significant intra-cascade spatial correlations consistent with strong elastic interaction between the defects.